Flood Potential Assessment of the Way Urang Sub-Watershed Based on Peak Discharge Using the Rational Method - Zuhrita, Anissa; Wahyu, Hyundra Zakiya Putri; Handayani, Nelly; Milla, Helny Yofin Mega; Safitri, Nabila Zalianti; Murti, Sigit Heru; Sudaryatno (Amcolabora, 2025)
Peak discharge is a key indicator for assessing flood potential in a river basin. This study estimates peak discharge in the Way Urang sub-watershed, Pesawaran, Lampung, by integrating remote sensing and Geographic Information Systems (GIS) to derive physical parameters that control surface runoff. The Rational Method was applied, combining the runoff coefficient (C), rainfall intensity (I), and drainage area (A). The runoff coefficient was calculated using the Cook Method, which takes into account soil type, slope gradient, vegetation density, and drainage density. Rainfall intensity was derived from daily records using the Mononobe equation, with time of concentration estimated from the Kirpich formula. Data sources include Sentinel-2 imagery, DEMNAS, rainfall records from 2014 to 2023, and field measurements. The results show a peak discharge of 217.19 m³/s for a basin area of 20.20 km², with a coefficient of variation (C) of 69.20% and an intensity (I) of 55.89 mm/h. High runoff reflects the combined effects of low-infiltration soils, steep slopes, and high annual rainfall. Morphometric measurements yielded a total channel cross-sectional area of 27.91 m² and an estimated bankfull discharge of 9.53 m³/s, indicating that the channel capacity is far below the peak discharge. This imbalance suggests a high flood potential in downstream areas, particularly in Bunut Village. The findings underscore the importance of integrating spatial data, field surveys, and remote sensing to analyze watershed physical characteristics and to support more effective, spatially informed flood planning and mitigation.